CRUSTAL MELTS BELOW 400 DEGREES CELSIUS - Sirbescu M.L.C.; Nabelek P.I. (My University, 2003)
We propose that the internally zoned, Li-bearing Tin Mountain pegmatite in the Harney Peak granite-pegmatite system of the Black Hills, South Dakota, crystallized from fluid-rich, compositionally complex melts at 400-350C. The low crystallization temperatures resulted from the combined fluxing effects of Li, B, P, H2O, and carbonate anions. The presence of hydrous silicate melts at temperatures of 350C is revealed by microthermometric data on primary fluid inclusions cogenetic with crystallized-melt inclusions. Mineral assemblages of the crystallized-melt inclusions and chemistry of bulk-fluid leachates indicate that the melts and fluids contained significant amounts of Li and Na as carbonates and/or borates that acted as powerful fluxes. The low temperatures give a new perspective on the stability of silicate melts in the crust. [PUBLICATION ABSTRACT]
Keywords: pegmatite; solidus; lithium bearing; ﬂuid inclusions; melt inclusions; carbonate ions